Stratigraphic Architecture and Sediment Facies of the Western Oak Ridges Moraine, Humber River Watershed, Southern Ontario - Russell, Hazen; Arnott, Robert; Sharpe, David (Géographie physique et Quaternaire, 2004)
AbstractThe Oak Ridges Moraine in southern Ontario is a ca. 160 km long east-west trending ridge of sand and gravel situated north of Lake Ontario. Study of the Oak Ridges Moraine in the Humber River watershed was undertaken to assess its role in the groundwater system of the buried Laurentian Valley. The Oak Ridges Moraine is interpreted to have been deposited in three stages. Stage I records rapid deposition from hyperconcentrated flows where tunnel channels discharged into a subglacial lake in the Lake Ontario basin. Low-energy basin sedimentation of Stage II was in a subglacial and ice-contact setting of a highly crevassed ice sheet. Stage III sedimentation is characterized by rapid facies changes associated with esker, subaqueous fan, and basinal sedimentation. Detailed sediment analysis challenges the concept that the Oak Ridges Moraine was deposited principally from seasonal meltwater discharges, climatic modulated ice-marginal fluctuations, or in an interlobate position. Instead it is interpreted to have formed in response to late-glacial ice sheet events associated with subglacial meltwater ponding, episodic and catastrophic subglacial meltwater discharge, and subsequent seasonal meltwater discharge. The moraine probably formed as the glacial-hydraulic system re-equilibrated to the presence of a thinned, grounded ice shelf and a subglacial lake in the Lake Ontario basin.